LA FLORA FÓSIL DE LA FORMACIÓN JEJENES (CARBONIFERO). IMPLICANCIAS PALEOCLIMÁTICAS y PALEOBIOGEOGRÁFICAS (Ameghiniana, 2014)
The fossil flora of the Jejenes Fonnation ineludes typical gondwanic cornponents (as Botrychiopsisv, together with sorne characteristic fonn genera of the pa1aeoequatorial Lower Carboniferous (as Triphyllopteris and Fryopsis), and cordaitalean leaves. New specimens from La Rinconada, San Juan province, (type locality of the Jejenes Fonnation) are described in this paper. The material incJudes new specimens of Triph yllopt eris cuyana and Fryopsis sp. cf. Fi frondosa, a complete frond assigned to Fryopsis sp., isolated pinnules which are assigned lo (?) Cardiopteridium sp., and ovules of strong palaeoequatorial affinities. The megafloral assemblage of the Jejenes Formation suggests a migration of Early Carboniferous laxa from the palaeoequalorial belt lo the south and (if the Jejenes Formation is of Late Carboniferous age) it would be a conservative flora exceptionally diversified. On the other hand, diversification of flora, large size of specimens and ocurrence of laxa of palaeoequatorial belt affinities at the highest levels of the sequence probably indicates the non-existence of glacial climatic conditions at that moment.